2018
DOI: 10.1159/000495400
|View full text |Cite
|
Sign up to set email alerts
|

4-Octyl Itaconate Activates Nrf2 Signaling to Inhibit Pro-Inflammatory Cytokine Production in Peripheral Blood Mononuclear Cells of Systemic Lupus Erythematosus Patients

Abstract: Background/Aims: Increased production of multiple pro-inflammatory cytokines, including tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and IL-6, plays an essential pathogenic role in the progression of systemic lupus erythematosus (SLE). Recent studies have characterized itaconate as a novel and potent nuclear-factor-E2-related factor 2 (Nrf2) activator that activates Nrf2 signaling by alkylating cysteine residues on Keap1 (Kelch-like ECH-associated protein 1). Methods: THP-1 human macrophages and periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 38 publications
8
58
0
Order By: Relevance
“…Our results are in accordance with those of other work indicating that DI limits the production of cytokines in LPS‐treated macrophages . In addition, OI, another itaconate derivative, downregulates the levels of cytokines in mononuclear cells …”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results are in accordance with those of other work indicating that DI limits the production of cytokines in LPS‐treated macrophages . In addition, OI, another itaconate derivative, downregulates the levels of cytokines in mononuclear cells …”
Section: Discussionsupporting
confidence: 93%
“…Immunostaining showed that DI treatment increased the accumulation of Nrf2 in the nuclei of infected HCECs. Our results are consistent with those of studies showing that a derivative of itaconate induces the nuclear accumulation of Nrf2 in human macrophages …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations